Entwicklung eines Messsystems zur modalbasierten Schädigungsanalyse von Brückenüberbauten - Kohm, Mareike (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung, 2022)
Bridges are key components of infrastructure networks, which are the basic prerequisite for a prospering economy. Regarding maintenance scheduling, profound knowledge of the current bridge condition is of high interest. In this work, a modal-based monitoring system is developed, which can augment the subjectively influenced visual inspection of bridge structures according to DIN 1076 by an objective sensor-based monitoring.